Prospects for the creation of national and supranational cryptocurrencies in the BRICS countries - O. M. Makhalina; V. N. Makhalina (Управление)
The article proposes to carry out the process of developing a new financial system of the BRICS States in the following sequence: to transfer foreign trade between the States to settlements in national currencies, with the subsequent development of its own unit of account, which will subsequently be able to replace the dollar and the Euro in mutual settlements within the BRICS; develop your own cryptocurrency or choose one of the existing cryptocurrencies, which for a certain period will be one of the possible elements of the settlement mechanism in the mutual trade of these five countries; to develop supra-national crypto-currency for the countries members of the BRICS. This process will be very complex, as it will require many technological, macroeconomic and organizational challenges.To solve the problem of building a new financial and monetary system of the BRICS countries, the article analyzes the actual level of digitalization of financial activities in the countries of the Association, on the basis of which proposals are developed and the following conclusions are formulated: crypto-currency operations are not completely prohibited in any of the States of the Association, and the prohibitions apply only to certain operations (ISO, mining, exchanges). Cryptocurrency is not recognized as a legal means of payment; in the BRICS countries there are no own, national cryptocurrencies, and only projects of future cryptocurrencies are developed, taking into account the features of the set goalsof economic development and management of cryptocurrency activities; the countries of the Association do not abandon the use of blockchain technology in the field of economy and Finance, as it ensures the openness and security of data storage, the creation of centralized exchanges, the exchange of goods and services; the BRICS countries should be interested in a gradual shift away from dollar dependence. The instruments of this movement are the national currency, its own, internal unit of account, its own national cryptocurrency, supranational cryptocurrency.